Obstacles Faced by DP3A in Providing Legal Protection for Child Molestation Victims - Rawung, Putri Alifia; Suyaman, Prahasti (MultiTech Publisher, 2024)
Child molestation is a serious crime that threatens the well-being and rights of children, causing serious trauma. In Indonesia, Law No. 35 of 2014 aims to protect children, with the Women's Empowerment and Child Protection Agency (DP3A) to handle cases. Data from DP3A Sukabumi shows 85 cases of child sexual violence throughout 2023 and 48 cases up to June 2024. This study finds DP3A Sukabumi faces several obstacles in providing legal protection for the victims. These include victims' fear of social stigma, lack of knowledge, distrust in the legal system, and threats from perpetrators, which hinder reporting. Additionally, DP3A struggles with a shortage of human resources and limited budget, reducing its capacity to effectively manage cases and support victims.